Risk Mitigation Of Sterile Linen Provision Process Of CSSD Rsud Dr. Soetomo Using House Of Risk Method - Hilmy, Andhika Rayhan; Lestari, Yetty Dwi (Southeast Asian Business Review, 2025)
The present research explores risk mitigation in the sterile linen provision process at the Central Sterile Supply Department (CSSD) of RSUD Dr. Soetomo, a leading referral hospital in East Indonesia. Addressing operational vulnerabilities in the sterilization process, this study adopts the House of Risk (HOR) methodology to proactively identify and minimize risks that may hinder service delivery. Utilizing a qualitative single-case study approach, data were gathered through in-depth interviews with eight informants directly or indirectly involved in the CSSD operational workflow. The analysis identified 13 critical risk agents, with boiler malfunction emerging as the highest-priority risk (ARPj: 2166), followed by inadequate implementation of Standard Operating Procedures (ARPj: 1374), and goods lift malfunction (ARPj: 1352). In the second phase of HOR, key preventive actions were proposed, including SOP Control, Monitoring & Internal Audit, Training & Development, and Digitalization. Among these, SOP Control was identified as the most effective strategy based on mitigation priority (ETDk: 44380.5). This study offers a structured framework to improve risk management and operational resilience in hospital sterilization services.